Policy options for the sustainable development of Zambia’s electricity sector - Bernard Tembo (Journal of Energy in Southern Africa, 2017)
This paper aims at understanding how Zambia’s electricity system would be affected by droughts (due to a dry year) and how the system’s adaptive capacity could be improved. Hydropower currently supplies 99% of the total electricity in Zambia, and concerns have been raised because many climate change studies project increased occurrences of dry years in the Southern Africa region. Different economic and climatic scenarios were explored to understand their impact on the development of Zambia’s power generation system, and what policies and strategies could be adopted to mitigate these impacts on security of supply and average generation costs, which directly affect the electricity price. The results show that a dry year has significant impact on the average generating cost since hydropower continues to dominate the system. Diversifying the system does not improve the adaptive capacity of the system but only increases the average cost of generating electricity in an average year. The most cost effective way of increasing the system’s adaptive capacity is by importing electricity and gradually increasing share of renewable and coal technologies in the system. Further research on how electricity trade in Southern Africa could be enhanced, should be done.